Reconstruction of the cell entry pathway of an extinct virus - Robinson-McCarthy, Lindsey R.; McCarthy, Kevin R.; Raaben, Matthijs; Piccinotti, Silvia; Nieuwenhuis, Joppe; Stubbs, Sarah H.; Bakkers, Mark J. G.; Whelan, Sean P. J. (PLoS pathogens, 2018)
Endogenous retroviruses (ERVs), remnants of ancient germline infections, comprise 8% of the human genome. The most recently integrated includes human ERV-K (HERV-K) where several envelope (env) sequences remain intact. Viral pseudotypes decorated with one of those Envs are infectious. Using a recombinant vesicular stomatitis virus encoding HERV-K Env as its sole attachment and fusion protein (VSV-HERVK) we conducted a genome-wide haploid genetic screen to interrogate the host requirements for infection. This screen identified 11 genes involved in heparan sulfate biosynthesis. Genetic inhibition or chemical removal of heparan sulfate and addition of excess soluble heparan sulfate inhibit infection. Direct binding of heparin to soluble HERV-K Env and purified VSV-HERVK defines it as critical for viral attachment. Cell surface bound VSV-HERVK particles are triggered to infect on exposure to acidic pH, whereas acid pH pretreatment of virions blocks infection. Testing of additional endogenous HERV-K env sequences reveals they bind heparin and mediate acid pH triggered fusion. This work reconstructs and defines key steps in the infectious entry pathway of an extinct virus.